Selective and Practical Oxidation of Sulfides to Diastereopure Sulfoxides: A Combined Experimental and Computational Investigation. Issue 1 (4th January 2013) - Bottoni, Andrea; Calvaresi, Matteo; Ciogli, Alessia; Cosimelli, Barbara; Mazzeo, Giuseppe; Pisani, Laura; Severi, Elda; Spinelli, Domenico; Superchi, Stefano
Abstract We describe an effective oxidation of diltiazem (DTZ)‐like molecules (a class of prochiral sulfides with potential pharmacological properties) using m‐chloroperbenzoic acid (MCPBA) as oxidant either in dichloromethane or methanol. An excellent diastereomeric excess of one sulfoxide has been observed "in the absence of any chiral auxiliary". The stereochemistry of the two diastereomeric sulfoxides has been determined by TDDFT simulations of the experimental electronic circular dichroism (ECD) spectra. A computational DFT study of the reaction mechanism shows that the attack of MCPBA on the two sulfide enantiotopic faces affords two preliminary complexes M1 and M1′. M1 is more stable than M1′ by 3.3 and 3.5 kcal mol−1 in dichloromethane and methanol, respectively, and after equilibration its population must be dominant. Two diastereomeric pathways originate from M1 and M1′ and give two diastereomeric sulfoxides with R and S configurations at the new chiral sulfur, respectively. Since TS (the transition state originating from M1) is more stable than TS′ (the energy gap is 0.7 kcal mol−1 in dichloromethane or methanol), following the Curtin–Hammett principle, the favoured path is the pro‐R channel (M1→TS→M2) affording the (Rc, Rs)‐2a′ product species in agreement with the observed diastereoselectivity. The M1–M1′ and TS–TS′ energy gaps are actually determined by the difference in the hydrogen bond network that features the two species even if the approaching orientation of the two molecules is governed by the interactions between the π systems of oxidant and substrate aromatic rings. The diastereomeric ratio computed on the basis of the energy difference between TS and TS′ (0.7 kcal mol−1) is 63:37, which must be compared to the experimental value 9:1. When we consider free energy differences (2.4 kcal mol−1 in vacuum and 2.9 kcal mol−1 in solution) this theoretical ratio becomes 85:15 and 89:11, respectively, in excellent agreement with the experimental value 9:1.